2005
DOI: 10.1021/ie058047m
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Melt Blowing of Hollow Fibers

Abstract: In commercial operation, a melt-blowing die is used to produce fine fibers that are solid, not hollow. In this paper, a model was developed to predict what would happen if hollow fibers were produced with a modified melt-blowing die. The model involved the simultaneous solution of the momentum, energy, and continuity equations. The model equations were solved numerically. Predicted parameters included fiber hollowness, fiber attenuation, vibration frequency, vibration amplitude, temperature, and stress. Hollow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Now, as Figures 4-6 show, the operation of a swirl die demonstrates the same trends as conventional melt blowing dies in response to changes in the four primary operating variables in melt blowing. With this similar behavior established, will swirl dies respond to hollowness in a manner similar to the predicted behavior (as described in Marla et al 11 ) for spinning hollow fibers with an annular die? If so, then what are the processing limits?…”
Section: Effect Of Changing the Mass Throughput Of The Polymersupporting
confidence: 63%
See 1 more Smart Citation
“…Now, as Figures 4-6 show, the operation of a swirl die demonstrates the same trends as conventional melt blowing dies in response to changes in the four primary operating variables in melt blowing. With this similar behavior established, will swirl dies respond to hollowness in a manner similar to the predicted behavior (as described in Marla et al 11 ) for spinning hollow fibers with an annular die? If so, then what are the processing limits?…”
Section: Effect Of Changing the Mass Throughput Of The Polymersupporting
confidence: 63%
“…Hollow Fibers Spun with Swirl Dies. Marla et al 11 modified their 3D melt blowing model for solid fibers (see Marla and Shambaugh 5 ) and simulated the manufacture of hollow fibers in the melt blowing process using an annular die configuration. They modeled the effect of hollowness on the fiber properties in the melt blowing process and drew several conclusions based on the predictions of the model.…”
Section: Effect Of Changing the Mass Throughput Of The Polymermentioning
confidence: 99%
“…This modeling has been done for both solid [13][14][15] and hollow fibers. 16 The interactions between air and a fiber have been examined for melt spinning, 17 in which the final fiber velocity is determined by the take-up roll. However, to the authors' knowledge, these interactions as they occur in the melt-blowing process have been studied in much less detail.…”
Section: Introductionmentioning
confidence: 99%
“…However, the models underpredicted the fiber whipping amplitude, which could be explained by the fact that the models did not include turbulence effects. By modifying the equations in the previous models, , Marla et al developed 1D and 3D models to predict hollow fiber production. Their simulation results indicated that hollow fibers have higher fiber amplitude and higher frequency than solid filaments, which could increase the quality of fiber laydown in terms of web uniformity.…”
Section: Fiber Formation Processmentioning
confidence: 99%